2023
DOI: 10.3390/agriculture13020380
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Modern Standardized Apple Orchard Flowering Monitoring Based on S-YOLO

Abstract: Monitoring fruit tree flowering information in the open world is more crucial than in the research-oriented environment for managing agricultural production to increase yield and quality. This work presents a transformer-based flowering period monitoring approach in an open world in order to better monitor the whole blooming time of modern standardized orchards utilizing IoT technologies. This study takes images of flowering apple trees captured at a distance in the open world as the research object, extends t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This indicates that GDD information can be used to do adaptability evaluation and kiwifruit commercial production. GDD may be a more accurate and reliable predictor of phenology for orchard planning, as Zhou et al [103] reported that monitoring fruit tree flowering can help manage orchards, which leads to increased yield and quality. In our studies, the study site Rawalpindi, which was colder than Chakwal, accumulated higher GDD than Chakwal.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that GDD information can be used to do adaptability evaluation and kiwifruit commercial production. GDD may be a more accurate and reliable predictor of phenology for orchard planning, as Zhou et al [103] reported that monitoring fruit tree flowering can help manage orchards, which leads to increased yield and quality. In our studies, the study site Rawalpindi, which was colder than Chakwal, accumulated higher GDD than Chakwal.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further verify the performance of the improved YOLOv8 model, this 2 study set up an ablation test to verify the performance of four groups of networks. YOLOv8+FocalModulation [26],YOLOv8 [27],YOLOV8+dysnakeconv [28] the algorithm in 2 3 this paper analyze the performance of four groups of networks from a quantitative perspective. The 1000 cherry images in the test set are objectively evaluated, and the evaluation indicators include model detection accuracy, average detection time, etc.…”
Section: Ablation Test Of Improved Yolo V8 Modelmentioning
confidence: 99%
“…However, the complex background environment, make it very difficult to identify small fruits in the early stage of fruits and vegetables. Extensive research has been done on fruit identification at home and abroad [ [9] , [10] , [11] , [12] ]. The fruit target recognition methods mainly include color difference method [ 13 ], K-means clustering method [ 14 ], fuzzy C-means method [ 15 ], K-Nearest Neighbor method, artificial neural network [ 16 ].…”
Section: Introductionmentioning
confidence: 99%